Taxonomic notes on the genus Chrysolaena (Vernonieae, Asteraceae), including a new species endemic to Paraguay - Dematteis, Massimiliano (2007)
The genus Chrysolaena H. Rob. (Vernonieae, Asteraceae) is redefined to include two taxa previously placed in Lessingianthus subgen. Oligocephalus H. Rob. Additionally, a new species of the genus endemic to eastern Paraguay is described and illustrated. The new species differs from its morphologically closest species, C. simplex (Less.) Dematteis, in its inflorescence of a single head, 3–4-seriate involucre, pilose corolla lobes and discolorous leaves, with silvery-greyish hairs on the abaxial surface.